Dynamic Dashboard and Database for People Development - Setiawan, Gary Oktovan; Rahardjo , Benedictus (European Journal of Scientific Exploration, 2020)
This research is intended to get the design of data recording system that will be recorded on the database and displayed on the dashboard for the department of Commercial Organizational Development in a company. Commercial Organizational Development is responsible for the development of workers who are under commercial. This is done by creating a database to store the data and create an interface so that data that has been collected can be seen easily. The design is done through the making of prototype which is then refined later that will be developed by the company with the making of platform and interface until next. Preliminary results showed a decrease in work time initially worked on for 5 hours 30 minutes decreased to 45 minutes.